CONSTRUING EFL STUDENTS’ BELIEFS ON THE INCLUSION OF INNER CIRCLE CULTURES IN ENGLISH LANGUAGE TEACHING - Ubaidillah, M. Faruq (Lingual Journal of Language and Culture; Vol 7 No 1 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v07.i01.p05, 2019)
Amidst the vast growth of English language and its teaching in EFL countries, an attentive action needs to be addressed to students (henceforth, participants) of English department regarding their belief systems of the Inner Circle cultures in the teaching of English. This study documented that those students put their preference on the inclusion of the Inner Circle cultures in English language teaching. Out of thirty four participants, 65% of them are of opinion that a language is bond with the culture. Then, the teaching of language per se should include its culture. One participant supported this, stating that the culture of the target language can refine their ability to understand the language well. Unlike those who favor the IC cultures, 21% of the participants disregard the issue. They, under the reason, felt the need of preserving their own local culture in ELT. Lastly, 15% of them, though small in number, put neutral beliefs on the issue. They contended that IC culture should only be introduced as an additional information in ELT as their own local cultures are more appropriate to learn. This paper ends with suggestions for policy makers to reframe the paradigm shift of English language teaching which puts local cultures at the front gate as well as English teachers to assist EFL students lift up their awareness on local culture teaching and learning.